In-Situ Impregnation of Copper Nanoparticles on Palm Empty Fruit Bunch Powder - Ridzuan, Ramli; Khan, Maksudur R.; R. M., Yunus; Ruey Ong, Huei; Rohaya, Mohamed Halim; Astimar, Abdul Aziz; Zawari, Ibrahim; Nahrul Hayawin, Zainal (Scientific Research, 2014)
Copper nanoparticles were impregnated onto oil palm empty fruit bunch (EFB) powders via in-situ sol-gel method. The impregnation and interfacial interaction of copper nanoparticles with EFB were analysed by fourier transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) and atomic force microscopy (AFM). The interaction of copper nanoparticles with the surface functional groups of EFB powders was identified by FTIR analysis. The peak shift of O-H and C-O functional groups indicated the interaction between EFB and copper nanoparticles. Besides that, XRD and EDX analysis confirmed the formation of copper nanoparticles on EFB powder. Due to the copper impregnation, the crystallinity of the EFB was increased as shown by XRD. The particles size of nanoparticles was analysed via TEM and AFM where the sizes were in the range of 60 - 100 nm. These findings strongly suggest that, copper nanoparticles impregnated EFB powders can be synthesized via insitu sol gel method.